Salvia miltiorrhiza ameliorates endometritis in dairy cows by relieving inflammation, energy deficiency and blood stasis - Tian, Shiyang; Liu, Tianyi; Jiang, Jingwei; Zhao, Xiting; Fan, Yunpeng; Zhang, Weimin; Ma, Wuren; Guo, Tingting; Wang, Weiling; Liu, Yingqiu (Frontiers in Pharmacology, 2024)
Introduction: According to traditional Chinese veterinary medicine, endometritis is caused by a combination of Qi deficiency, blood stasis, and external evil invasion. Salvia miltiorrhiza is a traditional Chinese medicine that counteracts blood stasis and has additional demonstrated effects in boosting energy and restraining inflammation. Salvia miltiorrhiza has been employed in many traditional Chinese prescriptions that have proven effective in healing clinical dairy cow endometritis. Methods: the in vivo effect of Salvia miltiorrhiza in treating endometritis was evaluated in dairy cows. In addition, bovine endometrial epithelium cell inflammation and rat blood stasis models were employed to demonstrate the crosstalk between energy, blood circulation and inflammation. Network analysis, western blotting, qRT-PCR and ELISA were performed to investigate the molecular mechanism of Salvia miltiorrhiza in endometritis treatment.Results: The results demonstrate that treatment with Salvia miltiorrhiza relieves uterine inflammation, increases blood ATP concentrations, and prolongs blood clotting times. Four of the six Salvia miltiorrhiza main components (SMMCs) (tanshinone IIA, cryptotanshinone, salvianolic acid A and salvianolic acid B) were effective in reversing decreased ATP and increased IL-1β, IL-6 and IL-8 levels in an in vitro endometritis model, indicating their abilities to ameliorate the negative energy balance and external evil invasion effects of endometritis. Furthermore, in a blood stasis rat model, inflammatory responses were induced in the absence of external infection; and all six SMMCs inhibited thrombin-induced platelet aggregation. Network analysis of SMMC targets predicted that Salvia miltiorrhiza may mediate anti-inflammation via the Toll-like receptor signaling pathway; antiaggregation via the Platelet activation pathway; and energy balance via the Thermogenesis and AMPK signaling pathways. Multiple molecular targets within these pathways were verified to be inhibited by SMMCs, including P38/ERK-AP1, a key molecular signal that may mediate the crosstalk between inflammation, energy deficiency and blood stasis.Conclusion: These results provide mechanistic understanding of the therapeutic effect of Salvia miltiorrhiza for endometritis achieved through Qi deficiency, blood stasis, and external evil invasion.